ANOMALI TUMPANG TINDIH PERATURAN MENTERI DAN PERATURAN DAERAH: TINJAUAN HIERARKI PERATURAN - Bagas Fadhilah; Fahmi Ramadhan Firdaus (Refleksi Hukum: Jurnal Ilmu Hukum, 2025)
This article addresses the normative conflict between Ministerial Regulations and Regional Regulations arising from the ambiguous position of Ministerial Regulations within Indonesia's regulatory hierarchy under Law Number 12 of 2011. This ambiguity generates disputes over authority between central and local governments, undermines legal certainty, and weakens regional autonomy. The article argues that resolving such disharmony requires three measures: explicit clarification of the position of Ministerial Regulations within the regulatory hierarchy; strengthening of substantive harmonization mechanisms; and limiting the subject matter of Ministerial Regulations so as not to encroach upon areas of attributed regional authority. These conclusions are reached through legal research employing a legislative approach, a conceptual approach applying Hans Kelsen's Stufenbau Theory, and a comparative approach drawing on Japan's regulatory harmonization practice.